2022
DOI: 10.1007/s11739-022-02945-7
|View full text |Cite
|
Sign up to set email alerts
|

Does the length of stay in hospital affect healthcare outcomes of patients without COVID-19 who were admitted during the pandemic? A retrospective monocentric study

Abstract: Uncertainties remain if changes to hospital care during the coronavirus disease (COVID-19) pandemic had an adverse impact on the care-quality of non-COVID-19 patients. We examined the association of hospital length of stay (LOS) with healthcare quality indicators in patients admitted with general medical conditions (non-COVID-19). In this retrospective monocentric study at a National Health Service hospital (Surrey), data were collected from 1st April 2019 to 31st March 2021, including the pandemic from 1st Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(23 reference statements)
3
4
0
Order By: Relevance
“…In addition, we have also shown a lower risk of mortality amongst non-COVID-19 patients admitted during the pandemic compared to those admitted before the pandemic, particularly if in the highest LACE index category. These findings are in consistent with our previous report [ 20 ] and suggest that the standard of care-quality of patients admitted with general medical conditions continued to be maintained, or even increased, during the pandemic.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we have also shown a lower risk of mortality amongst non-COVID-19 patients admitted during the pandemic compared to those admitted before the pandemic, particularly if in the highest LACE index category. These findings are in consistent with our previous report [ 20 ] and suggest that the standard of care-quality of patients admitted with general medical conditions continued to be maintained, or even increased, during the pandemic.…”
Section: Discussionsupporting
confidence: 93%
“…These factors were complications arising from primary diagnoses or MM, frailty necessitating integrated rehabilitation, and patient-centred needs. [13] Our findings were similar to a recent Singaporean study that showed how continuity of integrated care in the community was considerably affected during the COVID-19 pandemic. In their study, reluctance or hesitancy from formal and informal caregivers to accept community services due to fear of contracting COVID-19 infection resulted in many patients experiencing delayed LOS.…”
Section: Discussionsupporting
confidence: 90%
“…Prospective data of consecutive admissions to an acute general medical department in a Surrey, UK hospital, were collected from patients admitted before (1st April 2019 to 29th February 2020) and during the pandemic (1st March 2020 to 31st March 2021; Fluck et al, 2021Fluck et al, , 2022. The hospital is the largest provider of acute hospital services in Surrey, serving a population of 450 000.…”
Section: Study Design Participants and Settingmentioning
confidence: 99%